1999
DOI: 10.4269/ajtmh.1999.61.548
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of acute eosinophilic myositis attributed to human Sarcocystis parasitism.

Abstract: Abstract. Seven members of a 15-man U.S. military team that had operated in rural Malaysia developed an acute illness consisting of fever, myalgias, bronchospasm, fleeting pruritic rashes, transient lymphadenopathy, and subcutaneous nodules associated with eosinophilia, elevated erythrocyte sedimentation rate, and elevated levels of muscle creatinine kinase. Sarcocysts of an unidentified Sarcocystis species were found in skeletal muscle biopsies of the index case. Albendazole ameliorated symptoms in the index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
1
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 12 publications
2
78
1
12
Order By: Relevance
“…infection was reported and involved 7 of 15 U.S. military personnel who had operated in rural Malaysia. 10 More recently, outbreaks of symptomatic acute muscular sarcocystosis in foreign travelers to Tioman Island, off the east coast of peninsular Malaysia were reported. 11,12 We report two symptomatic cases of acute muscular sarcocytosis in which S. nesbitti has been identified.…”
mentioning
confidence: 99%
“…infection was reported and involved 7 of 15 U.S. military personnel who had operated in rural Malaysia. 10 More recently, outbreaks of symptomatic acute muscular sarcocystosis in foreign travelers to Tioman Island, off the east coast of peninsular Malaysia were reported. 11,12 We report two symptomatic cases of acute muscular sarcocytosis in which S. nesbitti has been identified.…”
mentioning
confidence: 99%
“…It indicates that muscular sarcocystosis may be a cause of eosinophilia. Sarcocystis might be an overlooked cause of unexplained eosinophilia and eosinophilic myositis (Arness et al, 1999;Abdul-Rahman et al, 2002). Tappe et al (2013) reported that eosinophilia is a hallmark of acute and not chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these are associated with parasitic infections as muscle sarcocystosis (Habeeb et al, 1996;Crum-Cianflone, 2008). Many cases have been recently reported and some are clinically diagnosed as eosinophilic myositis (Arness et al, 1999). Muscular sarcocystos is described in many parts of the world, 21% of the patients in Southeast Asia, 47% in U.S. military team in rural Malaysians, 19.8% in Malaysia, 60 cases in the United States and 26% patients in Iraq (Wong and Pathmanathan, 1992;Arness et al, 1999;Abdul-Rahman et al, 2002;Kiel, 2002;Al-Taee et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cysts contain many banana shaped bradyzoites of size ranging from 1-3μm. Other findings that can be seen in the muscle biopsy include myonecrosis, perivascular and interstitial inflammation, vasculitis and eosinophilic myositis [12]. Human muscular sarcocystosis is so rare in India with a few cases being reported across a wide range of age group [13].…”
Section: Case Reportmentioning
confidence: 99%